The importance of the main physiological groups of microorganisms in the change of physico-chemical forms of technogenic radionuclides in the sod-podzolic soil of the exclusion zone of the Chernobyl NPP - Tankevich, Elena; Nikitin, Aleksander; Kantsavaya, Irina; Симончик Yuliya (Journal of the Belarusian State University. Ecology, 2024)
The main sources of radioactive contamination of the soil and vegetation cover are global radioactive fallout from the atmosphere of long-lived radionuclides after nuclear tests, as well as emissions of man-made radionuclides associated with the work of industrial enterprises, accidents at nuclear power plants. Microflora plays an important role in the transformation of the physicochemical state of radionuclides in the soil. Depending on the type of soil and the microbial community inhabiting it, these processes can both accelerate and slow down. The study of this problem requires an integrated approach, with the organization of long-term monitoring. In this work, the influence of soil microorganisms of various physiological groups on the change of physicochemical forms of technogenic radionuclides of sod-podzolic sandy loam soil of the exclusion zone of the Chernobyl NPP was investigated. It was found that the greatest decrease in the specific activity of 137Cs in water-soluble form in sod-podzolic sandy loam soil is promoted by such groups of microorganisms as spore-forming ammonifiers – by 21,7 % and microbiological preparation EM-1 – by 52,1 % compared with the control sample. Ammonifying proteolytic microorganisms reduce the specific activity of the radionuclide in ion-exchange form by 12,5 %. In the variant of the experiment using EM-1 fertilizer, an increase in the specific activity of 137Cs in ion-exchange form was observed by 16,9 %.